2008
DOI: 10.1128/jb.01577-07
|View full text |Cite
|
Sign up to set email alerts
|

α-Tocopherol Is Essential for Acquired Chill-Light Tolerance in the Cyanobacterium Synechocystis sp. Strain PCC 6803

Abstract: Unlike Escherichia coli, the cyanobacterium Synechocystis sp. strain PCC 6803 is insensitive to chill (5°C) in the dark but rapidly losses viability when exposed to chill in the light (100 mol photons m ؊2 s ؊1 ). Preconditioning at a low temperature (15°C) greatly enhances the chill-light tolerance of Synechocystis sp. strain PCC 6803. This phenomenon is called acquired chill-light tolerance (ACLT). Preconditioned wild-type cells maintained a substantially higher level of ␣-tocopherol after exposure to chill-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
45
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 45 publications
(63 reference statements)
1
45
0
2
Order By: Relevance
“…Studies with Synechocystis sp. strain PCC 6803 (here referred to as Synechocystis) showed that a unicellular cyanobacterium could acquire chill (5°C)-light (100 mol photons m Ϫ2 s Ϫ1 ) tolerance after preconditioning at a suboptimal low temperature, such as 15°C (26). A similar phenomenon was also found in the bloom-forming species Microcystis sp.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…Studies with Synechocystis sp. strain PCC 6803 (here referred to as Synechocystis) showed that a unicellular cyanobacterium could acquire chill (5°C)-light (100 mol photons m Ϫ2 s Ϫ1 ) tolerance after preconditioning at a suboptimal low temperature, such as 15°C (26). A similar phenomenon was also found in the bloom-forming species Microcystis sp.…”
mentioning
confidence: 66%
“…A similar phenomenon was also found in the bloom-forming species Microcystis sp. (26). These findings suggest that cyanobacteria may develop the capability to overwinter in early winter, or before, when water temperatures decrease.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Yin 等通过对 PCC6803 的研究发现, 该藻株对低温光照条件敏感, 不利于藻株存活 [17] ; Yang 等进一步研究发现藻株内 α-维生素 E 含量增加对其存活率提升有较大影响 [18] ; 而 Wan 等的最新研究结果揭示了微囊藻在为期 31d 的底泥环境中, 显示出了一定的抗逆性, 且 PS II 活性能较快恢复 [19] . 泊富营养化调查规范》 (第二版) [20] ; 同时使用血球计数板对微囊藻细胞进行计数, 微囊藻细胞净复苏率定 义为每天装置内收集到的微囊藻细胞数除以装置的截面积(相当于底泥面积).…”
Section: 长 在世界范围内也属罕见 其水华优势种一年中大部分时间主要为铜绿微囊藻(Microcystis Aeruginosa)unclassified